1999
DOI: 10.1002/(sici)1096-9926(199909)60:3<117::aid-tera5>3.0.co;2-g
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology of abdominal wall defects, Hawaii, 1986-1997

Abstract: The various types of abdominal wall defects are considered to differ in their etiologies, a hypothesis suggested by differences in their epidemiologies. This study examined the impact of selected demographic factors on abdominal wall defects (omphalocele, gastroschisis, and body stalk anomaly) included in a birth defects registry in Hawaii from 1986–1997. The total prevalence for the various defects were: omphalocele (2.76 per 10,000 births, 95% confidence interval (CI), 2.14–3.50), gastroschisis (3.01, 95% CI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

12
63
1
1

Year Published

2000
2000
2014
2014

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 90 publications
(77 citation statements)
references
References 15 publications
12
63
1
1
Order By: Relevance
“…The prevalence of omphalocele has been reported to be 1.22-2.76 per 10,000 births, and gastroschisis, 0.94-3.01 per 10,000 births [3][4][5]. The exact etiology of these anomalies is unknown.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The prevalence of omphalocele has been reported to be 1.22-2.76 per 10,000 births, and gastroschisis, 0.94-3.01 per 10,000 births [3][4][5]. The exact etiology of these anomalies is unknown.…”
Section: Discussionsupporting
confidence: 92%
“…Therefore, the delivery and subsequent surgery can be planned and carried out in an interdisciplinary fashion. The mortality rate of omphalocele has been well known to be higher than that of gastroschisis [5,9,15,16]. Many studies demonstrated that this higher mortality was attributed to higher association of cardiac anomaly in omphalocele [17,18].…”
Section: Discussionmentioning
confidence: 99%
“…Much of the variation among states can be attributed to the method of case ascertainment and the case definition. States that use active case finding and that include cases from fetal deaths and live births, such as North Carolina (Laughon et al, 2003) and Hawaii (Forrester and Merz, 1999a), report relatively high prevalence rates (4.5 and 3.0/10,000 live births, respectively), while New York (Salihu et al, 2003), which uses passive case finding among live born infants, reports a relatively low rate (1.4/10,000).…”
Section: Introductionmentioning
confidence: 99%
“…The prevalence is also increasing in the United States, where the population-based rate of gastroschisis repairs was twofold higher in 2003 than 1996, with increases occurring in each census region (Alvarez and Burd, 2007). Utah (Hougland et al, 2005), Hawaii (Forrester and Merz, 1999a), New York (Salihu et al, 2003), Tennessee (Collins et al, 2007), California (Vu et al, 2008), and North Carolina (Laughon et al, 2003) reported increasing prevalence rates over the past decade.…”
Section: Introductionmentioning
confidence: 99%
“…8 The single investigation of this question in a statewide population of infants in the United States reported a modest increase between 1986 and 1997. 9 In this study, we sought to investigate changes in the birth prevalence of gastroschisis using data from a population-based state registry and data from a consortium of neonatal practices representing infants from across the United States.…”
Section: Introductionmentioning
confidence: 99%